Optimalisasi Pendapatan Usaha Melalui Media Digital Dengan Teknik Copywriting - Siti Nuke Nurfatimah; Enung Nurhayati; Syahrul Syarifudin (Universitas Serang Raya, 2026)
Abstract Lengkong Village, located in Kuningan Regency, is a member of the Digital Village community. However, unfortunately not many MSMEs in this village use digital media to market their products digitally. The lack of information, knowledge and limited capabilities are the reasons for implementing this PKM activity. Remembering that this strategy for utilizing digital technology is very important to help increase business income. This PKM activity aims to provide literacy regarding the importance of using digital technology, training on the use of digital media and supporting applications as well as providing assistance in designing product advertisements and applying copywriting techniques to create interesting content. This activity was attended by MSME actors and was carried out at the Lengkong Village Hall, Kuningan Regency. The method used in this PKM activity is an approach through providing literacy, training and mentoring. At the end of the activity, we also carried out an evaluation which showed that there was an increase in knowledge (the importance of digital technology to increase income) and ability (using the Canva application to create copywriting and content) in terms of utilizing this digital technology. Kata Kunci: Copywriting, Digital Marketing, Revenue